2021
DOI: 10.3390/diagnostics11060961
|View full text |Cite
|
Sign up to set email alerts
|

Using Anti-Malondialdehyde Modified Peptide Autoantibodies to Import Machine Learning for Predicting Coronary Artery Stenosis in Taiwanese Patients with Coronary Artery Disease

Abstract: Machine learning (ML) algorithms have been applied to predicting coronary artery disease (CAD). Our purpose was to utilize autoantibody isotypes against four different unmodified and malondialdehyde (MDA)-modified peptides among Taiwanese with CAD and healthy controls (HCs) for CAD prediction. In this study, levels of MDA, MDA-modified protein (MDA-protein) adducts, and autoantibody isotypes against unmodified peptides and MDA-modified peptides were measured with enzyme-linked immunosorbent assay (ELISA). To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…In our previous study, we had reported that the autoantibodies against four different MDA modified peptides may serve as biomarkers in diagnosing patients with CAD [ 23 ]. The MDA-modified positions were underlined: 76 -ADYEK HK VYACEVTHQGLSSPVTK- 99 (IGKC 76–99 ), 284 -LQHLENELT H DIITK- 298 (alpha-1-antitrypsin, A1AT 284–298 ), 824 -VSVQLEASPAFLAVPVE K - 841 (alpha-2-macroglobulin, A2M 824–841 ,), and 4022 -WNFYYSPQSSPD KK LTIF K - 4040 (apolipoprotein B-100, ApoB100 4022–4040 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we had reported that the autoantibodies against four different MDA modified peptides may serve as biomarkers in diagnosing patients with CAD [ 23 ]. The MDA-modified positions were underlined: 76 -ADYEK HK VYACEVTHQGLSSPVTK- 99 (IGKC 76–99 ), 284 -LQHLENELT H DIITK- 298 (alpha-1-antitrypsin, A1AT 284–298 ), 824 -VSVQLEASPAFLAVPVE K - 841 (alpha-2-macroglobulin, A2M 824–841 ,), and 4022 -WNFYYSPQSSPD KK LTIF K - 4040 (apolipoprotein B-100, ApoB100 4022–4040 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, different classifiers have been chosen to predict CAD according to their performance. Reports from previous studies done by Hsu et al (2021) show that random forest can be used as an effective algorithm to predict CAD based on the area under the receiver operating characteristic (ROC) curve (AUC) around 0.94. Muhammad et al (2021) used machine learning predictive models for CAD prediction, and among the used models, random forest stands as the best model with an AUC of 0.92.…”
Section: Related Workmentioning
confidence: 99%
“…Authors have performed the machine learning models for coronary artery disease in Nigeria and the RF model emerged as the best model for performing the predictions, in terms of accuracy followed by the best sensitivity results for the support-vector machine learning model [30]. The RF classifier achieved remarkable results for the AUC value for predicting the coronary artery stenosis in Taiwanese patients with coronary artery disease [31].…”
Section: Literature Reviewmentioning
confidence: 99%